Implantable Electroceutical Approach Improves Myelination by Restoring Membrane Integrity in a Mouse Model of Peripheral Demyelinating Neuropathy. Issue 32 (17th August 2022) - Intisar, Aseer; Shin, Hyun Young; Kim, Woon‐Hae; Kang, Hyun Gyu; Kim, Min Young; Kim, Yu Seon; Cho, Youngjun; Mo, Yun Jeoung; Lim, Heejin; Lee, Sanghoon; Lu, Q. Richard; Lee, Yun‐Il; et al.
Abstract: Although many efforts are undertaken to treat peripheral demyelinating neuropathies based on biochemical interventions, unfortunately, there is no approved treatment yet. Furthermore, previous studies have not shown improvement of the myelin membrane at the biomolecular level. Here, an electroceutical treatment is introduced as a biophysical intervention to treat Charcot‐Marie‐Tooth (CMT) disease—the most prevalent peripheral demyelinating neuropathy worldwide—using a mouse model. The specific electrical stimulation (ES) condition (50 mV mm −1, 20 Hz, 1 h) for optimal myelination is found via an in vitro ES screening system, and its promyelinating effect is validated with ex vivo dorsal root ganglion model. Biomolecular investigation via time‐of‐flight secondary ion mass spectrometry shows that ES ameliorates distribution abnormalities of peripheral myelin protein 22 and cholesterol in the myelin membrane, revealing the restoration of myelin membrane integrity. ES intervention in vivo via flexible implantable electrodes shows not only gradual rehabilitation of mouse behavioral phenotypes (balance and endurance), but also restored myelin thickness, compactness, and membrane integrity. This study demonstrates, for the first time, that an electroceutical approach with the optimal ES condition has the potential to treat CMT disease and restore impaired myelin membrane integrity, shifting the paradigm toward practical interventions for peripheral demyelinating neuropathies. Abstract : An electroceutical approach to improve myelination in a mouse model of Charcot‐Marie‐Tooth disease is presented. Following an optimal electrical stimulation (ES) condition, myelination enhancement is confirmed at in vitro, ex vivo, and in vivo stages. Biomolecular analysis shows restored myelin membrane integrity via improvements in PMP22 and cholesterol distribution. Implantable ES to the mouse promotes gradual rehabilitation of behavioral phenotypes.